Analysis Of The Effectiveness Of E-Commerce Utilization In Developing Marketing For SME Products (Case Study Of SMEs In The Tanjung Morawa District) - Kurniawan, Syahreza Wahyu; Lubis, Muhammad Arifin (Jurnal Ekonomi, 2024)
In the current era of globalization, technology plays a pivotal role in various aspects of life, particularly in business activities. E-commerce has emerged as a prominent platform, facilitating product selection, transactions, and interactions between buyers and sellers through internet-connected media. This research explores the effectiveness of e-commerce in developing product marketing for micro, small, and medium enterprises (UMKM), focusing on a case study in the Tanjung Morawa District. Employing qualitative descriptive research, this study aims to provide insights into the impact of e-commerce on UMKM marketing strategies. Data collection involves direct interviews with UMKM owners. The findings reveal that e-commerce offers significant advantages for UMKM, enabling them to overcome barriers such as distance and time in conducting business activities. Through e-commerce, UMKM can reach a broader consumer base and enhance their competitiveness in the market. However, challenges such as technological barriers and online visibility persist. Overall, the study underscores the importance of e-commerce as a strategic tool for UMKM development and offers recommendations for its effective implementation.